2006
DOI: 10.1021/bc0502107
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Loaded Poly(γ-glutamic acid)-poly(lactide) Nanoparticles as a Targeted Drug Delivery System against Cultured HepG2 Cells

Abstract: The study was to develop paclitaxel-loaded formulations using a novel type of self-assembled nanoparticles that was composed of block copolymers synthesized from poly(gamma-glutamic acid) and poly(lactide) via a simple coupling reaction. The nanoparticles (the NPs) were prepared with various feed weight ratios of paclitaxel to block copolymer (the P/BC ratio). The morphology of all prepared nanoparticles was spherical and the surfaces were smooth. Increasing the P/BC ratio significantly increased the drug load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…Previous attempts have been largely limited to design of small molecule paclitaxel derivatives, such as ester paclitaxel derivatives and phosphate paclitaxel derivatives, etc (2)(3)(4)(5). In recent years, use of macromolecules for the targeted delivery of anticancer agents has generated considerable interest regarding enhancing therapeutic efficacy and reducing systemic side effects, and some satisfactory results have been obtained (6)(7)(8)(9). Apparently, it would have been desirable to develop drug delivery systems which would be more soluble than paclitaxel, but which, upon hydrolysis under physiological conditions, would exhibit the same or similar level of antitumor activity as free paclitaxel.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts have been largely limited to design of small molecule paclitaxel derivatives, such as ester paclitaxel derivatives and phosphate paclitaxel derivatives, etc (2)(3)(4)(5). In recent years, use of macromolecules for the targeted delivery of anticancer agents has generated considerable interest regarding enhancing therapeutic efficacy and reducing systemic side effects, and some satisfactory results have been obtained (6)(7)(8)(9). Apparently, it would have been desirable to develop drug delivery systems which would be more soluble than paclitaxel, but which, upon hydrolysis under physiological conditions, would exhibit the same or similar level of antitumor activity as free paclitaxel.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some research studies indicated that only a small amount of NPs without galactosamine was internalized into hepatoma cells, whereas the galactosamine-modified NPs lead to high targeting to hepatic tumor and facilitate their cellular uptake. 73,74 Hence, lactose and galactosamine are also potential ligands to ASGPR. To develop galactosylated polymer for drug and gene delivery to hepatoma cells and hepatocytes, Narain's group synthesized 2-lactobionamidoethyl methacrylamide including Gal residues, 75,76 which could be used in composing copolymer through reversible addition-fragmentation chain transfer polymerization technique.…”
mentioning
confidence: 99%
“…Numbers of hydrophobic groups or PEG-b-PLL pDNA Electrostatic interactions A D h of ca. 100 nm, a low absolute ζ-potential value and excellent colloidal stability [42] ε-PLL-DDSA-SA BSA; lysozyme Electrostatic interactions EE reached almost 100% for BSA and 90% for lysozyme [28] ε-PLL-g-OSA Curcuminoids Hydrophobic interaction DL of 5.3%; ε-PLL-g-OSA micelles increased solubility of curcuminoids in water by 5000 folds [84] γ-PGlu-b-PLLA PTX Hydrophobic interaction DL of 6.1%; as feed weight ration of PTX to copolymer, DL of PTX-loaded micelle increased [85] γ-PGlu-g-L-PAE ODN-protamine polyplex Electrostatic interactions EE of 80%; the amount of ODN in the micelles and the EE were increased as the ratio of N/P increased [86] PEG-(PCL-b-γ-PGlu) DOX Electrostatic; hydrophobic interaction DL of 12.14% and EE of 97.22%; γ-PGlu block exhibited shrinking and aggregation at low pH which led to a slow drug release [87] polymeric segment have been exploited to modify its α-carboxylic groups or terminal amino group, synthesizing amphiphilic grafted copolymer or block copolymer [23]. These hydrophobic segments included poly(L-lactide) or poly(D-lactide), cholesterol [24], and Lphenylalanine ethylester (L-PAE) [25].…”
Section: Amphiphilic Isomerism Poly(amino Acid) Copolymersmentioning
confidence: 99%